1998
DOI: 10.1002/(sici)1096-9101(1998)22:4<212::aid-lsm5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

780 nm low power diode laser irradiation stimulates proliferation of keratinocyte cultures: Involvement of reactive oxygen species

Abstract: Background and Objective The purpose of this study was to determine irradiation parameters of a 780 nm low power CW diode laser (6.5 mW) leading to enhanced proliferation of cultured normal human keratinocytes (NHK). The possible role of reactive oxygen species (ROS) in this response was evaluated. Study Design/Materials and Methods: NHK were exposed to a single dose of 0 to 3.6 J/cm2 (0–180 sec) of irradiation. Proliferation parameters studied were: incorporation of 3H‐thymidine during 6–24 hr following irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
170
4
19

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(200 citation statements)
references
References 26 publications
(47 reference statements)
7
170
4
19
Order By: Relevance
“…Although this diode laser has an output power of 100 mW, the laser light reached the MDPC-23 cells on the bottom of each well with a final power of 70 mW. The cells were irradiated every 24 hours totalizing 3 applications during 3 consecutive days [21,22,[26][27][28]. After the last irradiation cycle, the 24-well plates were maintained in the humidified incubator (Isotemp; Fisher Scientific, Pittsburgh, PA, USA) with 5% CO 2 and 95% air at 37 • C for an additional period of 3 hours [8].…”
Section: Lllt On the Mdpc-23 Cellsmentioning
confidence: 99%
“…Although this diode laser has an output power of 100 mW, the laser light reached the MDPC-23 cells on the bottom of each well with a final power of 70 mW. The cells were irradiated every 24 hours totalizing 3 applications during 3 consecutive days [21,22,[26][27][28]. After the last irradiation cycle, the 24-well plates were maintained in the humidified incubator (Isotemp; Fisher Scientific, Pittsburgh, PA, USA) with 5% CO 2 and 95% air at 37 • C for an additional period of 3 hours [8].…”
Section: Lllt On the Mdpc-23 Cellsmentioning
confidence: 99%
“…[5][6][7] Some specific types of laser can also stimulate fibroblasts to synthesize and deposit collagen matrix. [8][9][10] A number of in vitro investigations using a wide range of cell cultures have provided different data concerning cell proliferation 11,12 and differentiation, 13 DNA and bone protein synthesis, 1,[14][15][16] and bone tissue formation without genotoxic or cytotoxic damage. 17 Unfortunately, these studies have particular irradiation setups and different methodologies, so that the results obtained cannot be compared with or extrapolated to others.…”
mentioning
confidence: 99%
“…Previously published results have also reported stimulatory effects of 780 nm light on neuronal tissue in vivo 37,38 . In vitro studies have demonstrated the involvement of reactive oxygen species in the process 39 . However, the detailed mechanisms by which NIR stimulation affects gene transcription and other cellular activities are currently unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanisms by which NIR stimulation affects gene transcription and other cellular activities are currently unresolved. Current data suggests the interplay of different effects in the stimulation, including photon absorption within chromophores in the mitochondria (almost 50% of the energy at 780 nm might be absorbed by cytochrome c oxidase) 37,[39][40][41] , changes in membrane permeability to calcium 37 and inhibition of inflammatory activity in the cells 37 .…”
Section: Discussionmentioning
confidence: 99%